KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA DALAM MENYELESAIKAN SOAL ALJABAR BERKONTEKS KEMARITIMAN DENGAN ADVERSITY QUOTIENT KATEGORI CLIMBERS - Ulfarianti, Finia; Ramadhona, Rezky; Hilda Syani Putri, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study seeks to portray the extent to which student comprehend mathematical concepts when confronted with algebra problems set within a maritime context, focusing specifically on the topic of Three Variable Linear Equation Systems (SPLTV), and examines through the climbers category of the adversity quotient (AQ) framework. The concern motivating this investigation stems from the persistent difficulties faced by student at SMA Negeri 2 Tanjungpinang in working with mathematical notation, linking concepts to the situations described in problems, and piecing together information presented in word-based questions. Adopting a qualitative descriptive design, the study centered on two students identified as belonging to the climbers category, drawn from a group of 37 students in class X.12 through an AQ questionnaire, a written test, and semi-structured interviews; the collected data were then processed through the stages of reduction, presentation, and drawing conclusions. The results indicate that climbers student demonstrated a fairly strong and steady level of conceptual understanding, particularly in carrying out procedures algorithmically and expressing concepts through mathematical representations, such as formulating SPLTV models from maritime-related data. Even so, these students still encountered obstacles when requites to concepts in their own terms or to distinguish between examples and non-examples, as they tended to treat variables as names of commodities rather as unknown quantities to be determined. These outcomes point to the fact that a high adversity quotient does not automatically ensure equal mastery across all indicators of conceptual understanding.